Molar incisor hypomineralization: Prevalence, severity and associated aetiological factors in children seeking dental care at Armed Forces Hospital Jazan, Saudi Arabia - Mohammed Zameer; Syed Wali Peeran; Syed Nahid Basheer; Syed Ali Peeran; Gulam Anwar Naviwala; Sameen Badiujjama Birajdar (Elsevier, 2024)
Background: The prevalence of molar incisor hypomineralisation (MIH) varies worldwide. In Saudi Arabia, data about this condition is limited to a few cities. Aim: To evaluate the prevalence, severity and associated aetiological factors of MIH in children seeking dental care in Armed Forces Hospital, Jazan, Saudi Arabia. Methodology: Participants were recruited by convenience sampling according to eligibility criteria. Diagnostic criteria used were according to the molar incisor hypomineralisation severity scoring system (MIH-SSS). Demographic data and past medical history were recorded using a carefully organised questionnaire, and MIH causal factors were evaluated. Results: A total of 1405 children participated in the study. Among the permanent first molars, mandibular teeth were more frequently affected by MIH than maxillary teeth. In the permanent central incisors group, maxillary teeth were more frequently involved than mandibular teeth, whereas lateral incisor was the least affected among the tooth types in all four quadrants. MIH had more frequently involved all four molars (66.1%), and two associated central incisors were found (31.3%). MIH in the incisors had mild to moderate severity, whereas molars presented with severe defects. Among prenatal factors, maternal anaemia and vitamin D deficiency, out-of-perinatal factors, caesarean delivery, low birth weight and perinatal jaundice, and early childhood tonsillitis and early childhood anaemia were the significant associated factors for MIH development. Conclusion: The prevalence of MIH was 8%, and maxillary incisors and mandibular first molars were frequently affected. Children with MIH showed prenatal, perinatal and postnatal aetiological factors involved in the development of MIH.